Multiculturalism in South Korea: New Myth and Reality (The Case of Marriage Migrants) - Yem, N. B. (Journal of Oriental Studies, 2016)
the article studies the results of the policy of multiculturalism in south Korea for example, marriage migrants from asia. addressing demographic problems, the state and society is faced with problems of adaptation of migrants.